Search for the doubly heavy baryons Ω0bc and Ξ0bc decaying to Λ+cπ− and Ξ+cπ− - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Chinese physics. C, High energy physics and nuclear physics, 2021)
The first search for the doubly heavy baryon and a search for the baryon are performed using collision data collected via the experiment from 2016 to 2018 at a centre-of-mass energy of , corresponding to an integrated luminosity of 5.2 . The baryons are reconstructed via their decays to and . No significant excess is found for invariant masses between 6700 and 7300 , in a rapidity range from 2.0 to 4.5 and a transverse momentum range from 2 to 20 . Upper limits are set on the ratio of the and production cross-section times the branching fraction to ( ) relative to that of the ( ) baryon, for different lifetime hypotheses, at 95% confidence level. The upper limits range from to for the ( ) decay, and from to for the ( ) decay, depending on the considered mass and lifetime of the ( ) baryon.